(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2019)
The article is devoted to the study of spatial characteristics of the autobiographical novels by Amélie Nothomb, the Belgian French-speaking writer. The main protagonist of Amélie Nothombs’s autobiographical novels is similar to the image of the author for their biographical characteristics. Its living space consisted of real author’s one, there was a constant alternation of open and closed spaces. A complex antagonistic relationship between the external (relative to main character) world, that lives his life, and internal world, in which the main character lives, are typical for all of the autobiographical heritage of writer.